2010
DOI: 10.1007/s10517-010-0986-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Preliminary Load of Macrophages with Silicium Dioxide on Phagocytosis of BCG Strain Micobacteria by Macrophages and Antimicrobial Activity

Abstract: We studied the effect of preliminary loading of peritoneal macrophages with silicium dioxide on in vitro viability, phagocytosis of BCG strain mycobacteria, and the capability to destroy the phagocytosed mycobacterium tuberculosis. It was shown that preliminary loading of macrophages with silicium dioxide did not reduce their viability and stimulated phagocytosis of BCG strain mycobacteria, but reduced their antibacterial activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…Because PRRs, such as C-type lectin receptors, SRs, TLRs, NOD-like receptors, and RIG-I like receptors, play a prominent role in the activation of AMs and subsequent cross-talk with innate and adaptive immune cells, how a macrophage reacts to a given stimulus depends greatly on the diverse range of PRRs expressed on the cell’s surface ( 43 , 44 ). In the case of concomitant or sequential exposure to two distinct pathogens, the capacity of macrophages to recognize, phagocytose, and appropriately respond to a second stimuli may be compromised by stimulant-induced changes in the profile of PRRs ( 45 ) – thus altering susceptibility to disease. TLRs, which recognize microbial molecules, are major triggers of innate responses (e.g., enhanced costimulatory molecule expression, cytokine secretion, production of reactive oxygen species, and antimicrobial mediators) and thus modulate adaptive immunity by influencing macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
“…Because PRRs, such as C-type lectin receptors, SRs, TLRs, NOD-like receptors, and RIG-I like receptors, play a prominent role in the activation of AMs and subsequent cross-talk with innate and adaptive immune cells, how a macrophage reacts to a given stimulus depends greatly on the diverse range of PRRs expressed on the cell’s surface ( 43 , 44 ). In the case of concomitant or sequential exposure to two distinct pathogens, the capacity of macrophages to recognize, phagocytose, and appropriately respond to a second stimuli may be compromised by stimulant-induced changes in the profile of PRRs ( 45 ) – thus altering susceptibility to disease. TLRs, which recognize microbial molecules, are major triggers of innate responses (e.g., enhanced costimulatory molecule expression, cytokine secretion, production of reactive oxygen species, and antimicrobial mediators) and thus modulate adaptive immunity by influencing macrophage functions.…”
Section: Discussionmentioning
confidence: 99%
“…The tuberculosis loading in rats was consistent with the progress of silicosis. Interestingly, an in vitro study by Shkurupy et al 13,14 demonstrated that preliminary loading of macrophages with silicium dioxide reduced their antibacterial activity, implying that the cytotoxicity of silica dust to macrophage was the main reason for the damage to the anti-tuberculosis function. However, little was known about the detail injury mechanism and immune regulation.…”
Section: Discussionmentioning
confidence: 99%
“…Immunocytochemical studies of MP were carried out by the indirect immunocytochemical method [8]. Macrophages in cultures were fi xed with neutral formalin (4% water solution), the enzymes were retrieved with Triton X-100 (0.3% solution in phosphate buffer, pH 7.2).…”
Section: Methodsmentioning
confidence: 99%
“…Studies of MP secretory activity were carried out by the same protocol as studies of MP expression of enzymes [8]. Sterile millipore membranes of standard size (10×10 mm) were put into Petri dishes (40 mm) instead of slides.…”
Section: Methodsmentioning
confidence: 99%